2016
DOI: 10.1038/srep37970
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical properties of distinct fibrillar polymorphs of the protein α-synuclein

Abstract: Alpha-synuclein (α-Syn) is a small presynaptic protein of 140 amino acids. Its pathologic intracellular aggregation within the central nervous system yields protein fibrillar inclusions named Lewy bodies that are the hallmarks of Parkinson’s disease (PD). In solution, pure α-Syn adopts an intrinsically disordered structure and assembles into fibrils that exhibit considerable morphological heterogeneity depending on their assembly conditions. We recently established tightly controlled experimental conditions al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 44 publications
4
70
0
Order By: Relevance
“…The IR and AFM results indicated that an increase in parallel b-sheet contents is the main factor affecting the protein fibrils (Makky, Bousset, Polesel-Maris, & Melki, 2016;Ruggeri et al, 2016). Moreover, our results strongly suggest that oligomerization and/or aggregation is mainly associated with the formation of b-sheet.…”
Section: Discussionmentioning
confidence: 51%
“…The IR and AFM results indicated that an increase in parallel b-sheet contents is the main factor affecting the protein fibrils (Makky, Bousset, Polesel-Maris, & Melki, 2016;Ruggeri et al, 2016). Moreover, our results strongly suggest that oligomerization and/or aggregation is mainly associated with the formation of b-sheet.…”
Section: Discussionmentioning
confidence: 51%
“…Similar values have been reported by other authors for different polymorphs of α‐Syn formed under different solution conditions. [ 25 ] This result indicates that the amyloids formed in absence of AWI are more flexible, have a contour length often higher than their L p , and are therefore more susceptible to thermal breakage, supporting the occasional detection of red‐only fibrils in the dSTORM and correlative LM‐SEM images (panels 3D–F, 4J and 4L). Furthermore, the persistence length of semiflexible polymers L p relates to the Young Modulus E and the second area moment of inertia I via L p = EI / K B T where K B and T are the Boltzmann constant and absolute temperature.…”
Section: Resultsmentioning
confidence: 57%
“…α-Syn was incubated in buffer A to obtain the fibrillar polymorph “fibrils” (50 mM Tris–HCl, pH 7.5, 150 mM KCl), in buffer B for “ribbons” (5 mM Tris–HCl, pH 7.5), in buffer C for “fibril-65” (20 mM MES pH6,5, 150 mM NaCl) and in buffer D for “fibril-91” (20 mM KPO4 pH9.1), at 37 °C under continuous shaking in an Eppendorf Thermomixer set at 600 r.p.m for 4–7 days 16 , 40 .…”
Section: Methodsmentioning
confidence: 99%